Chemometric technique for the optimization of chromatographic system: Simultaneous HPLC determination of Rosuvastatin, Telmisartan, Ezetimibe and Atorvastatin used in combined cardiovascular therapy - V. Sree Janardhanan; R. Manavalan; K. Valliappan (Arabian Journal of Chemistry, 2016)
Developed and optimized a validated isocratic reverse phase HPLC separation of Rosuvastatin, Telmisartan, Ezetimibe and Atorvastatin in pharmaceutical preparation using response surface methodology. The separation was carried out by using phenomenex C18 column (15 cm × 4.6 mm id, 5 μm particle size) and UV detection at 239 nm. The ranges of the independent variables used for the optimization were MeCN: 33–38%, buffer conc.: 10–20 mM and flow rate: 1–2 ml/min. The influence of these independent variables on the output responses: capacity factor of the first peak (k1), resolutions of the 2nd and 3rd peak (Rs2,3), and capacity factor of the fifth peak (k5) were evaluated. Using this strategy, a mathematical model was defined and a response surface was derived for the separation. The three responses were simultaneously optimized by using Derringer's desirability functions. Optimum conditions chosen for the assay were MeCN, MeOH, 20 mM K2HPO4 (pH 3.0 ± 0.2) solution (34.27:20:45.73 v/v/v) and flow rate 2 ml/min. Total chromatographic analysis time per sample was approximately 10 min. The optimized assay condition was validated as per the ICH guidelines and applied for the quantitative analysis of Rosavel EZ, Avas-EZ and Lipisar 20 tablet. The developed method was simple, accurate and precise. Hence, it can be employed for the routine analysis in quality control laboratories.